Nanoemulsion formulation of Vernonia amygdalina delile against Botrytis cinerea causing gray mold disease in tomato and their effects on postharvest quality - Yusoff, Siti Fairuz (2022)
Gray mold disease caused by Botrytis cinerea is one of the significant postharvest losses mostly observed during tomato storage and transportation. Synthetic fungicide is currently used to control this disease, but it poses adverse effects to human health, environment, and development of resistance to synthetic fungicides. V. amygdalina extract showed antifungal activity which could be a sustainable tool as biofungicide for plant disease management. The present study aimed to screen phytochemical compounds in V. amygdalina leaf extract, develop nanoemulsion formulations containing V. amygdalina crude extract, evaluate antifungal activities of nanoemulsions against B. cinerea and preserve postharvest quality. Ten fungal isolates were obtained from symptomatic tomato fruits sampled from Cameron Highlands, Pahang, Malaysia. Fungal colonies on PDA appeared cottony and white to gray color. Conidia were ovoid in shape, hyaline, and measured 10.03-16.08 × 7.37-11.15 μm. To confirm molecular identification, the primer pair ITS4/ITS5 of rDNA was used for amplification and sequencing of isolates. The sequences with GenBank accession MT012053-MT012062 were the closest match to Botrytis cinerea with query coverage was 98-99%. Based on pathogenicity assay, the isolates indicated highly pathogenic with the maximum disease severity was 90% (Isolate MT012058). In vitro test showed leaf extracts of aqueous, hexane, dichloromethane (DCM) and methanol at 100-500 mg/mL were significantly inhibited mycelial growth of B. cinerea. DCM was the most effective, which inhibited up to 75.74% of the mycelial growth of B. cinerea. The top major chemical compounds identified in DCM extract using GC-MS analysis were squalene, phytol, triacontane, heptacosane, and neophytadiene. For in vivo bioassay, the fruits treated with dichloromethane extract at 400 and 500 mg/mL showed the lowest disease incidence with mild severity of infection. The SEM observation proved that the treatment altered the fungal morphology, which leads to fungal growth inhibition. The nanoemulsion system containing oil, water and surfactant was obtained using spontaneous emulsification technique by employing four surfactants. From eight selected formulations, two formulations, F5 and F7 showed stability in storage, remarkable thermodynamic stability, small-sized droplet (66.44 and 139.63 nm), highly stable in zeta potential (−32.70 and −31.70 mV), low in polydispersity index (0.41 and 0.40 PdI), low in viscosity (4.20 and 4.37 cP) and low in surface tension (27.62 and 26.41 mN/m) compared to other formulations. In vivo efficacy on tomato fruits showed F5 formulation had a fungicidal activity against B. cinerea with zero disease incidence and severity, whereas F7 formulation reduced 62.5% disease incidence compared to a positive control with scale 1. F5 and F7 nanoemulsions exhibited higher enzyme activities of PAL, POD, and SOD compared to benomyl and control fruits. Meanwhile, F5 nanoemulsion triggered significantly higher PPO and CAT activities compared to F7 nanoemulsion. F5 nanoemulsion showed delays in fruit maturity, minimal weight loss, slower changes in firmness, TA, SSC and pH, retained the vitamin C content, fair in phenolic content and execute high antioxidant activities. In conclusion, F5 nanoemulsion has a fungicidal effect on B. cinerea, induces higher defense-enzymes activities, and gives optimum postharvest quality in tomato. Thus, F5 nanoemulsion containing V. amygdalina leaf extract could be useful for inhibiting gray mold disease on tomato fruit and has the potential as a natural antifungal agent.